Hubungan Tingkat Pengetahuan dan Motivasi Wanita Usia Subur dengan Pemeriksaan Inspeksi Visual Asam Asetat di Wilayah Kerja Puskesmas Deli Tua - Hutabarat, Vitrilina -; Sitepu, Stefani Anastasia; Natalia, Kristin; Hafiza, Hilda Laila (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
Hutabarat, Vitrilina. The Relationship Between Knowledge Level and Motivation of Women of Childbearing Age with Acetic Acid Visual Inspection Examination in the Puskesmas Work Area. skripsi, Department of Midwifery, Faculty of Midwifery, Deli Husada Health Institute, Old Deli. Based on a preliminary study conducted at the Deli Tua Health Center in 2023, there are 50 people who undergo IVA examination screening from a total of 100 women of childbearing age who visit the Deli Tua Health Center. The purpose of this study is to determine the relationship between the level of knowledge and motivation of WUS with IVA examination in the work area of the Old Deli Health Center. This type of research is an analytical survey with a cross sectional study design. The population is 100 women of childbearing age who visit the Deli Tua Health Center from January to June 2023. The sampling technique is 50 people. Data analysis using Chi-Square test with confidence level (α=0.05). There is a relationship between the level of knowledge and motivation of WUS with IVA examination in the working area of the Deli Tua Health Center in 2023 with a value of p=0.001 where p < α (0.05). Therefore, it is expected to be more active Women of childbearing age to increase Knowledge and Motivation carried out by Health workers and Women of childbearing age are expected to seek information about cervical health and early detection of cervical cancer in mass and print media